The effects of Performance-based Assessment to Enhance Teaching and Learning Science (ForPS) Model on science process skills and science concepts understanding of secondary students in Kinta District of Perak. - Hj Abdullah, Eftah Moh; Lebar, Othman; Abd. Shukor, Abd. Aziz (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Four classes of Form One students of four schools in Kinta district, State of Perak, Malaysia participated in a five weeks intervention designed to enhance teaching and learning science with Performance-based Assessment to Enhance Teaching and Learning Science (ForPS) Model. Teachers in intervention classrooms were implemented an assessment approach that incorporated the use of instructions based on curriculum-specifications from Ministry of Education and the performance-based assessment module into individual and classroom instructional planning. During the intervention period, control groups continued to use of instruction based on a curriculum-specifications from Ministry of Education and the use of a memory-based traditional testing procedures adopted by the school, which included the use of the assessment of learning developed by the subject teachers’. Intervention groups demonstrated significant improvements on some dimensions of performance as measured by the Integrated Science Process Skills and Science Concepts Understanding, whereas control groups exhibited no significance change. Implications for practice are discussed.